Pengungkapan Environmental, Sosial and Governance Terhadap Financial Distress Perusahaan Yang Terdaftar Dalam Indeks IDX ESG Tahun 2024 - Nabila Khairunnisa; Erma Setiawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study investigates the influence of Environmental, Social, and Governance (ESG) disclosures on financial distress among companies listed in the Indonesia Stock Exchange (IDX) ESG Index in 2024. Using a quantitative explanatory approach, the research analyzes 32 firms selected through purposive sampling. Secondary data from financial statements and annual reports were used, with ESG performance measured based on environmental practices, stakeholder relations, and governance mechanisms, as provided by IDX and Morningstar Sustainalytics. Financial distress was assessed using the Debt to Asset Ratio (DAR). Multiple linear regression and descriptive statistics were employed for data analysis, preceded by classical assumption tests to ensure model validity. The results indicate that environmental disclosure has no significant effect on financial distress, while social and governance disclosures significantly reduce financial distress. These findings highlight the importance of social and governance factors in mitigating financial risks. The study is limited by the availability of complete ESG scores, suggesting the need for broader sectoral coverage and longer observation periods in future research.